Asymmetric effects of native and exotic invasive shrubs on ecology of the West Nile virus vector Culex pipiens (Diptera: Culicidae) - Allison M. Gardner; Brian F. Allan; Lauren A. Frisbie; Ephantus J. Muturi (Parasites & Vectors, 2015)
Abstract Background Exotic invasive plants alter the structure and function of native ecosystems and may influence the distribution and abundance of arthropod disease vectors by modifying habitat quality. This study investigated how invasive plants alter the ecology of Culex pipiens, an important vector of West Nile virus (WNV) in northeastern and midwestern regions of the United States. Methods Field and laboratory experiments were conducted to test the hypothesis that three native leaf species (Rubus allegheniensis, blackberry; Sambucus canadensis, elderberry; and Amelanchier laevis, serviceberry), and three exotic invasive leaf species (Lonicera maackii, Amur honeysuckle; Elaeagnus umbellata, autumn olive; and Rosa multiflora, multiflora rose) alter Cx. pipiens oviposition site selection, emergence rates, development time, and adult body size. The relative abundance of seven bacterial phyla in infusions of the six leaf species also was determined using quantitative real-time polymerase chain reaction to test the hypothesis that variation in emergence, development, and oviposition site selection is correlated to differences in the diversity and abundance of bacteria associated with different leaf species, important determinants of nutrient quality and availability for mosquito larvae. Results Leaf detritus from invasive honeysuckle and autumn olive yielded significantly higher adult emergence rates compared to detritus from the remaining leaf species and honeysuckle alleviated the negative effects of intraspecific competition on adult emergence. Conversely, leaves of native blackberry acted as an ecological trap, generating high oviposition but low emergence rates. Variation in bacterial flora associated with different leaf species may explain this asymmetrical production of mosquitoes: emergence rates and oviposition rates were positively correlated to bacterial abundance and diversity, respectively. Conclusions We conclude that the displacement of native understory plant species by certain invasive shrubs may increase production of Cx. pipiens with potential negative repercussions for human and wildlife health. These findings may be relevant to mosquito control and invasive plant management practices in the geographic range of Cx. pipiens. Further, our discovery of a previously unknown ecological trap for an important vector of WNV has the potential to lead to novel alternatives to conventional insecticides in mosquito control by exploiting the apparent “attract-kill” properties of this native plant species.